(untitled) (KULT_online, 2015)
In his monograph, Rainer Guldin takes a closer look at three types of landscape: mountain, forest and river in their function as national identity metaphors for Switzerland, Germany and Austria. A fourth focus is dedicated to the metaphor of aerial roots in terms of identities of exile and migration. He presents a great number of examples from public life and the arts, areas in which these metaphors have been used. For all of the metaphors it proves correct that landscapes in this sense are flexible regarding their multiple meanings, focusing different aspects and usable for different narrations.